Intravascular oesophageal variceal pressure (IOVP) assessed by endoscopic fine needle puncture under basal conditions, Valsalva's manoeuvre and after glyceryltrinitrate application. Issue 5 (May 1985) - Staritz, M; Poralla, T; Meyer zum Büschenfelde, K H
Abstract : A simple and safe procedure providing sensitive and reproducible direct measurement of intravascular oesophageal variceal pressure (IOVP) during routine oesophagoscopy is described. The method requires only commercially available equipment. First results were obtained in 16 patients with oesophageal varices caused by liver cirrhosis (Child's A) can be summarised as follows: intravascular oesophageal variceal pressure was nearly identical in different varices of the single patient. Varices grade III exhibited a significantly higher intravascular oesophageal variceal pressure than varices grade II (22.7 +/- 2.5 vs 15.7 +/- 0.6 mmHg, p less than 0.05). After Valsalva's manoeuvre there was a remarkable increase in intravascular oesophageal variceal pressure by 13.6 +/- 1.0 mmHg irrespective of the variceal size. The high intravascular oesophageal variceal pressure values observed in grade III varices during the rise of the intraabdominal pressure may indicate an important risk factor for variceal haemorrhage. Glyceryltrinitrate (1.2 mg sprayed onto the tongues of 14 patients) very effectively lowered the intravascular oesophageal variceal pressure from 22.8 +/- 2.0 to 12.0 +/- 0.4 mmHg in grade III varices, and from 16.3 +/- 0.4 to 10.0 +/- 0.4 mmHg in grade II varices (p less than 0.005 in both groups). We conclude that this method provides a suitable tool to study the effect of drugs with presumed influence on the oesophageal variceal pressure and that the impressive effect of glyceryltrinitrate in lowering intravascular oesophageal variceal pressure warrants further study on the effect of longer acting nitrates on intravascular oesophageal variceal pressure, and the rebleeding rate after oesophageal variceal haemorrhage.